Analisis Perlindungan Hukum terhadap Korban Transmisi Informasi Elektronik yang Melanggar Kesusilaan dan Mengandung Pemerasan (International Forum of Researchers and Lecturers, 2025)
The rapid development of information and communication technology not only brings a positive impact on various aspects of life, but also gives rise to new forms of cybercrime. One of the criminal acts that is increasingly prevalent is the transmission of electronic information that violates morality and contains elements of extortion. The lack of optimal psychological support and legal assistance also worsens the impact experienced by victims. Therefore, strategic steps are needed both preventive and repressive in handling cybercrime. This study aims to thoroughly examine the forms of legal protection available to victims, both in terms of normative legal frameworks, implementation by law enforcement officials, and mechanisms for restoring victims' rights through normative and empirical juridical research methods, as well as interviews with related parties.